(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Comprehensive field and laboratory studies were undertaken toinvestigate the performance of some crops on salt-affected soils in Sudan.To separate salinity and sodicity indicators some laboratory studies wereconducted on soils equilibrated with mixed NaCl-CaCl 2 solutions. Therelative hydraulic conductivity (RHC) or diffusivity increased withincrease in total salt concentration (C) and decrease in exchangeablesodium percentage (ESP). A dispersion index (DI), a swelling index (SI),shrinkage volume and modulus of rupture increased with increase in ESPand decrease in C. The data showed a highly significant linear decrease inRHC with increase in DI or SI. The threshold salt concentrations (THC),which gave 75% of the highest RHC, and ESP relationships, wereobtained for samples from an Aridisol and a Vertisol soils.. The salinityprofile obtained after intermittent leaching with water suggested thepresence of a desalinized zone followed by a salinized one with thehighest salt concentration below the wetting front. The depth of thedesalinized zone increased significantly with increase of the amount ofwater stored (r2 = 0.968) and the length of the wetting front (r2 = 0.974).Soil amendments promoted salt leaching in the following order: Sand>chicken manure> water hyacinth> gypsum> dry sewage> farm yardmanure> control. Cumulative evaporation (E) for the various amendments